1989
DOI: 10.3354/dao006201
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the control of bacterial kidney disease of salmonid fishes

Abstract: ABSTRACT. Bacterial kidney disease of salmonid fishes, caused by Renibactenum salrnoninarum, was first reported more than 50 yr ago; nevertheless, large gaps persist in our knowledge of the infectionparticularly in methods for its control. In the 1950's, principal control measures consisted of prophylactic or therapeutic feeding of sulfonamides, which were later supplanted by the antibiotic erythromycin. Chemotherapy has effected some reduction of mortality, but benefits are typically transient and mortality u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
70
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 57 publications
(98 reference statements)
0
70
1
Order By: Relevance
“…Injection of erythromycin into the 'dorsal sinus' of maturing female salmon is a recommended procedure for reducing pre-spawning mortalities due to BKD (Groman & Klontz 1983, Evelyn 1988, Elliott et al 1989. It has been shown that this procedure results in the deposition of erythromycin in the egg, and that the drug persists within the yolk material of the eggs and sac fry at levels greater than the reported in vitro minimum inhibitory concentration (MIC) (Bullock & Leek 1986, Evelyn et al 1986a, Armstrong et al 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Injection of erythromycin into the 'dorsal sinus' of maturing female salmon is a recommended procedure for reducing pre-spawning mortalities due to BKD (Groman & Klontz 1983, Evelyn 1988, Elliott et al 1989. It has been shown that this procedure results in the deposition of erythromycin in the egg, and that the drug persists within the yolk material of the eggs and sac fry at levels greater than the reported in vitro minimum inhibitory concentration (MIC) (Bullock & Leek 1986, Evelyn et al 1986a, Armstrong et al 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Control of both the disease and the dissemination of the agent remains difficult due to the ability of the bacterium to be vertically transmitted from parents to progeny inside the eggs (Bullock et al 1978, Evelyn et al 1984, 1986b, Lee & Evelyn 1989, Pascho et al 1991 and to survive intracellularly within host cells (Young & Chapman 1978, Gutenberger et al 1991, thus reducing bacterial exposure to the host immune defenses and any therapeutants. An effective vaccine is not yet available (Elliott et al 1989) so avoidance of horizontally transmitted Rs (Mitchum & Sherman 1981, Bell et al 1984 and of vertically transmitted Rs is still a primary management strategy. In addition to a water supply free of Rs, avoidance has largely been attempted by using eggs from certified Rs-free fish stocks or by manipulation of Rs-positive broodstocks to reduce vertical transmission to the progeny.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial kidney disease (BKD) caused by Renibacterium salmoninarum (Rs) continues to be a serious disease concern in salmonid culture worldwide (Fryer & Sanders 1981, Sanders & Barros 1986, Elliott et al 1989. Control of both the disease and the dissemination of the agent remains difficult due to the ability of the bacterium to be vertically transmitted from parents to progeny inside the eggs (Bullock et al 1978, Evelyn et al 1984, 1986b, Lee & Evelyn 1989, Pascho et al 1991 and to survive intracellularly within host cells (Young & Chapman 1978, Gutenberger et al 1991, thus reducing bacterial exposure to the host immune defenses and any therapeutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial kidney disease is one of the most difficult bacterial diseases to control in salmonid aquaculture facilities due in part to 2 unusual pathogenic mechanisms of the causative agent, Renibacterium salmoninarum (Elliott et al 1989). First, R. salmoninarum can 'E-mail: wiensg@ohsu.edu "Present address: Department of Veterinary Medicine, National Chung Hsing University, 250 Kuo Kuang Road, Taichung, Taiwan 40227, ROC be vertically transmitted from female fish to offspring via intracellular infection of the egg (Evelyn et al 1984(Evelyn et al , 1986.…”
Section: Introductionmentioning
confidence: 99%